Study on the preparation of manganese oxide filter media for catalytic oxidation removal of ammonium and manganese in high alkalinity groundwater: The effect of copper and cobalt doping. (15th September 2022) - Cheng, Ya; Xiong, Weiyao; Huang, Tinglin; Wen, Gang
Abstract: Owing to the low efficiency of catalytic oxidation of ammonium and manganese in high alkalinity groundwater by manganese oxide filter column, the effect of doping copper (Cu) and cobalt (Co) on catalytic activity was investigated. A pilot-scale filter column system was used in this experiment. The catalytic oxidation activities of manganese oxide filter media prepared at different Cu and Co concentrations (0, 0.1, 1.0 mg/L) in raw water were compared. The results showed that the removal efficiency of ammonium by the filter column increased from 65% to 100% due to low Cu doping, while the removal efficiency of manganese decreased from 95% to 60% due to high Cu doping. Low Co doping was beneficial to the start-up period of the filter column and the effluent ammonium concentration reached the standard on the 8th day. In addition, X-ray diffraction (XRD) and Scanning electron microscopy coupled energy dispersive spectroscopy (SEM-EDS) results showed that the high alkalinity of water led to the formation of a large amount of calcium carbonate on the surface of the filter media. Combined with X-ray photoelectron spectroscopy (XPS) analysis, it was found that the conversion of different valence manganese species caused by Cu and Co doping and the Cu and Co elements with different valence were the key factors determining the catalytic activity of manganese oxide filter media. Cu 2+ /Cu + and Co 3+ /Co 2+ electron cycles also participated in the electron transfer process of catalytic reaction. This study provides a research idea for solving the pollution problem of ammonium and manganese in high alkalinity water. Graphical abstract: Image 1 Highlights: High alkalinity obstructed the formation of ammonium removal activity. Different Cu doping amounts affected the manganese removal activity. Low Co doping shortened the start-up period of the filter column. The influence mechanism of Cu/Co doping in high alkalinity was proposed.